Cloud Storage Ethics in Industrial Engineering: A Comparative Analysis of Microsoft OneDrive and SharePoint - Afrianto, Riki; Nusivera, Sari; Haikal, Hikam (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
This study investigates the technical, ethical, and organizational implications of adopting Microsoft OneDrive and SharePoint within industrial engineering. Both platforms operate under Microsoft’s enterprise cloud infrastructure but differ significantly in governance design and ethical alignment. SharePoint’s hierarchical structure enables effective compliance, accountability, and workflow automation, making it suitable for regulated industrial environments. In contrast, OneDrive prioritizes user flexibility and mobility, which, while enhancing convenience, increases risks related to data misuse, shadow IT, and inconsistent policy adherence. Through a qualitative descriptive approach involving practitioners and academic users, the study identifies that organizational ethics, privacy management, and governance transparency are decisive factors in maintaining digital integrity. The findings indicate that technical safeguards such as encryption and access control must be reinforced by ethical responsibility and user education. Furthermore, sustainable cloud governance requires continuous monitoring, multi-factor authentication, and transparent data policies that respect user privacy and organizational accountability. The study concludes that OneDrive and SharePoint should function as complementary systems—balancing autonomy with oversight—to promote ethical, secure, and efficient collaboration in industrial digital ecosystems.